Regression analysis of flow parameters at high Mach numbers - Al-Khalifah, Turki; Aabid, Abdul; Khan, Sher Afghan (Solid State Technology, 2020)
Analysis of flow parameters, base pressure, is a critical component. For the convergent-divergent nozzle with abrupt expansion in an axisymmetric conduit, Microjets' effect as a control mechanism is tested experimentally. The control in the form of a 1 mm diameter orifice is extended at a 90-degree interval along the nozzle's exit diameter. The flow parameters considered are the Mach (M), the NPR, and the geometric variables considered are the L/D ratio of the three related parameters chosen for the design of experiments (DOE). The prime objective of the research is to explore the affected parameter in the regulation of base pressure. In two ways, the tests were carried out: without and with microjets. An L27 orthogonal series, multiple linear regression, and validation experiments were conducted to evaluate the experimental findings. In making accurate predictions for both cases, the established models are statistically acceptable and accomplished. According to the present findings, it is obvious that the L / D ratio is the most critical effect on the highest rise or decline of pressure at the base for a given parameter.